Midwest Ecological Study Outlined the Neighbourhood Literacy Environment and the Inequitable Access Children Have to Books in Public Library Branches / Crosh, C., Hutton, J., Szumlas, G., Xu, Y., Beck, A., & Riley, C. (2022). Inequities in public library branch access and children’s book circulation in a Midwestern American city. The International Journal of Information, Diversity, & Inclusion (IJIDI), 6(3), 68-81. https://doi.org/10.33137/ijidi.v6i4.38127 - Prince, Nandi (Evidence Based Library and Information Practice, 2023)
Objective – To explore the impact of the neighbourhood literacy environment (NLE) by examining associations between public library locations, book circulation rates, and neighbourhood racial composition.Design – An ecological study using aggregated data sources.Setting – Forty selected neighbourhood public libraries in the state of Ohio, United States of America.Subjects – Analysis of (1) existing circulation statistics from January 2014 to December 2018 for the neighbourhoods of Cincinnati and Hamilton Public Libraries; and (2) the American Community Survey (ACS) data from 2018.Methods – Among the key components studied for the population was the NLE, which the authors defined as access to literacy materials in a neighbourhood. The data the authors examined for the targeted populations were race, age, poverty level, and library location. The two groups of variables computed were: (1) the connection between circulation rates of children’s books and child poverty; (2) the connection between circulation statistics and the proportion of people who self-identify as Black in the neighbourhood. Additionally, the researchers used the Spearman’s rank order correlation coefficient (rs) to measure the relationships between the correlating variables within each neighbourhood library branch – number of books circulated per child; the census data of children who self-identified as Black; and the children who were designated as 20% below the federal poverty level (FPL). The Chi-square test was used to calculate associations between access to a library branch and child poverty in each neighborhood. In this study, the researchers only looked at the associations between variables at an aggregate level. The authors defined the terms they used in the study: (1) children were ages 0-18 years; (2) children’s books were literature intended for an audience from 0-18 years old; (3) the definition of poverty was taken from the U.S. Census and classified as neighborhoods with 20% of children below the FPL.Main Results – There were 40 library branches that served 81 neighbourhoods, of which there was only a 38% distribution in the high-poverty areas, compared with 58% for the low. Approximately 24 million books were circulated during the 5-year period of 2014 -2018. The median circulation rate per child at the neighbourhood level was 22 books. The results showed steep variations in circulation rates per child across branch locations; the numbers range from 3 to 98 books per child across neighborhoods. The authors indicated that the increases and decreases in the circulation rates were tied to branch location and the area’s socioeconomic status. The primary finding of the data analyzed was a negative correlation between the population identified as Black/African American and lower circulation rates in poorer neighbourhoods.Limitations identified by the authors were (1) the allocation of literacy resources per branch was unknown; (2) the in-library book user statistics in high-poverty neighbourhoods may not be accurately documented; (3) the precise allocations for literacy funds and the use of in-library resources for developing literacy skills need further study.Conclusion – The authors noted that race, economic status, and proximity to public libraries were pertinent factors in understanding inequitable access to books for children in the neighbourhoods studied. The NLE was an important dynamic beyond the home; the availability of books and engagement with them were contributing factors to the development of literacy skills. The associations observed between the variables indicated that improving the NLE matters and libraries must mindfully work to alleviate the disproportionately lower levels of access to books and their unfavorable outcome for children in low-income areas.